قاعدة: "فتح الذرائع" وأثرها في إثبات النسب للولد غير الشرعي في ماليزيا : دراسة فقهية تحليلية - Abdus Salam bin Abdul Rashid (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research aims to study the principle of Fath al-Dhara'i or Opening the Means from the Syari'ah perspective, its authority among Usul al-Fiqh scholars, and to discuss its theoretical relationship with related terms namely maṣlahah, ḍarurah, ḥajah, and rukhṣah. From the aspect of practicality, this research deals with the observation on the implementation of this principle in the issue of establishing the genealogical relationship (nasab) of an illegitimate child among Muslims in Malaysia. Based on the current situation, ascribing the lineage of the child and registering without associating him to his biological father will cause several problems that may impact his life significantly. However, affiliating the child to his father; the fornicator, when he acknowledges him may also lead to negative effects that need to be examined carefully. The researcher adopted the inductive method to gather all the information related to the topic as well as descriptive approach to depict the real meaning of Fath al-Dhara'i and its position in Syari'ah and to explain what is the definition of an illegitimate child. The analytical and comparison approaches also were adopted in discussing the authority of the principle among scholars, and the view of Muslim jurists as well as Islamic Religious Offices of Malaysia on the issue of affiliating the child to his biological father together with comparison between the good and evil that could probably resulted from the implementation of the principle. Among the important findings of this research is the principle of Fath al-Dhara'i is founded on the judgment of possible results of actions in which it aims to achieve the tangible benefits and prevent the greater evil based on presumptive certainty and not merely imaginative uncertainty even though the actions are prohibited from the very beginning. Besides, the acknowledgement (al-Istilhaq) from the biological father before the judge whereby the mother is not married or owned through milk al-Yamin could be considered as the sole alternative to be relied on in establishing the paternity of the illegitimate child in order to ensure his benefits. This acknowledgement is more justified and it will assist in opening the means of good and righteousness and it is necessary to do something in which the required demand cannot be accomplished without it.